A 3-Year Single Center Experience With Left Atrial Pressure Remote Monitoring: The Long and Winding Road - Restivo, Attilio; D'Amario, Domenico; Paglianiti, Donato Antonio; Laborante, Renzo; Princi, Giuseppe; Cappannoli, Luigi; Iaconelli, Antonio; Galli, Mattia; Aspromonte, Nadia; Locorotondo, Gabriella; Burzotta, Francesco; Trani, Carlo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Despite continuous advancement in the field, heart failure(HF) remains the leading cause of hospitalization among the elderly and the overall first cause of hospital readmission in developed countries. Implantable hemodynamic monitoring is being tested to anticipate the clinical exacerbation onset, potentially preventing an emergent acute decompensation. To date, only pulmonary artery pressure(PAP) sensor received the approval to be implanted in symptomatic heart failure patients with reduced ejection fraction. However, PAP's indirect estimation of left ventricular filling pressure can be inaccurate in some contexts. Methods: The VECTOR-HF study(NCT03775161) is examining the safety, usability and performance of the V-LAP system, a latest-generation device capable of continuously monitoring left atrial pressure(LAP). In our center, five advanced HF patients have been enrolled. After confirmation of the transmitted data reliability, LAP trends and waveforms have guided therapy optimization. The aim of this work is to share clinical insights from our center preliminary experience with V-LAP application. Results: Over a median follow-up time of 18 months, LAP–based therapy optimization managed to reduce intracardiac pressure over time and no hospital readmission occurred. This result was paralleled by an improvement in both functional capacity(6MWT distance 352.5±86.2 meters at baseline to 441.2±125.2 meters at last follow-up) and quality of life indicators(KCCQ overall score 63.82±16.36 vs 81.92±9.63; clinical score 68.47±19.48 vs 83.70±15.58). Conclusion: Preliminary evidence from V-LAP application at our institution support a promising efficacy. However, further study is needed to confirm the technical reliability of the device and to exploit the clinical benefit of left-sided hemodynamic remote monitoring.